Status prawny konsumenta jako strony umowy o kredyt indeksowany/ denominowany do franka szwajcarskiego - Zandecki, Jacek (Studia Prawa Publicznego, 2019)
In this study the legal status of a consumer as a party to the loan agreement indexed to the CHF is presented. During legal disputes, the subject of many controversies is the existence or the lack of the consumer status. This issue is of high procedural importance as it decides about the formal possibility of applying Article 3851 § 1 of the civil code (k.c.) and relying at the same time on the abusive nature of contractual clauses. In the article, the period that could be examined regarding the consumer status has been discussed in detail, indicating first of all that only the circumstances preceding the conclusion of the agreement and accompanying it influence the status of the consumer as provided under Article 221 k.c. The status of the consumer exists in when the objective prerequisites defined in art. 221 k.c. are fulfilled. The performance of the loan agreement has no direct influence on the issue and circumstances connected therewith and may be applied exclusively for the evidence purposes in the scope of facts and intentions of the natural person upon concluding the agreement. It was also raised that assessing or ‘valuing’ consumers due to the personal features (education, employment, practice) is not allowed and has no legal effect in the context of Article 221 k.c. The pattern “of the enlightened consumer” having its justification in the scope of interpretation of Article 385 § 2 k.c. has no application to the interpretation of Article 221 k.c. nor does the application of Article 3851 k.c. No features of a natural person prejudge either in plus, or in minus the status of the consumer. The fact that the property for which a loan has been taken out will be leased has no influence on the status of the consumer if the consumer being a natural person had a consumer status when concluding the agreement. Pursuant to the lex retro non agit principle the status of a consumer cannot be lost with retrospective force.